(untitled) (Scientific journal of the Fergana State University, 2023)
In the 1920s, many local young people from Turkestan, Bukhara, and Khorezm were sent abroad to study. Among these young people, there were a small number of girls. They studied in Germany in such fields as medicine, pedagogy, and education. The article is devoted to the study abroad of Khairiniso Majidkhanova, who studied at the teachers’ seminary in Darmstadt. It provides a scientific analysis of the problems, achievements and origins of the educational process of Khairiniso Majidkhanova. The article uses primary archival sources and scientific literature on this topic.